Interleukin-6 and interleukin-10 gene polymorphisms and the risk of further periodontal disease progression - Georgios Chatzopoulos; Aikaterini-Ellisavet Doufexi; Larry Wolff; Anastasia Kouvatsi (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract: Susceptible genotypes to periodontal disease are associated with disease onset and progression. The aim of this study was to examine the effect of gene polymorphisms on the risk of further disease progression and the need for further treatment among adults with chronic periodontal disease. Sixty-seven patients diagnosed with chronic periodontitis were grouped according to genotype status and risk of further progression of disease and tooth loss. All individuals were clinically evaluated for probing pocket depth, clinical attachment loss and bleeding on probing at baseline and 45 days after treatment. Blood samples were collected at baseline and genotyping of the polymorphisms in IL-6 (rs1800796) and IL-10 (rs1800872) genes were performed by PCR. Following DNA separation and genotyping, 65.7% of the patients were homozygous carriers of the IL-6 −572G and 49.3% were carriers of the IL-10 −592A allele. Individuals at risk of disease progression ranged from 7.5% to 62.7% based on the criteria used. Carriers of the IL-10 −592A allele were significantly associated with BOP ≥ 30% and therefore exhibited a higher risk of further periodontal breakdown (p = 0.018) with an odds ratio of 1.18. None of the other definitions of disease progression were significantly associated with the examined IL-6 and IL-10 genotypes (p > 0.05). IL-10 polymorphism was associated with an increased risk of further disease progression and the potential need for further treatment following non-surgical periodontal treatment. Susceptible IL-6 genotypes were not associated with the risk of persisting or recurrent disease activity.